2018
DOI: 10.1002/jcsm.12310
|View full text |Cite
|
Sign up to set email alerts
|

Treating cachexia using soluble ACVR2B improves survival, alters mTOR localization, and attenuates liver and spleen responses

Abstract: BackgroundCancer cachexia increases morbidity and mortality, and blocking of activin receptor ligands has improved survival in experimental cancer. However, the underlying mechanisms have not yet been fully uncovered.MethodsThe effects of blocking activin receptor type 2 (ACVR2) ligands on both muscle and non‐muscle tissues were investigated in a preclinical model of cancer cachexia using a recombinant soluble ACVR2B (sACVR2B‐Fc). Treatment with sACVR2B‐Fc was applied either only before the tumour formation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
167
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(193 citation statements)
references
References 71 publications
25
167
1
Order By: Relevance
“…A similar pattern was also described in human cancer, in which muscle protein synthesis rates were shown to be increased, decreased, or unchanged (46). On the other hand, most of the studies involving chemotherapy administration to healthy animals have reported reduced rates of muscle protein synthesis (13, 17, 29). The present study shows a severe depression of protein synthesis in both untreated and chemotherapy‐treated tumor‐bearing mice, consistent with reduced food intake.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was also described in human cancer, in which muscle protein synthesis rates were shown to be increased, decreased, or unchanged (46). On the other hand, most of the studies involving chemotherapy administration to healthy animals have reported reduced rates of muscle protein synthesis (13, 17, 29). The present study shows a severe depression of protein synthesis in both untreated and chemotherapy‐treated tumor‐bearing mice, consistent with reduced food intake.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cancer cachexia at least, this is not a definite finding, since muscle protein synthesis has been reported to increase, decrease, or remain unchanged (4). Data obtained studying experimental model systems have provided contrasting information: reduced protein synthesis has been observed in mice hosting the C26 or the Lewis lung carcinomas (LLC) (9,87,136), while normal anabolic potential has been shown by rats bearing the Yoshida AH-130 hepatoma (30). The situation is far from being clear also in cancer patients.…”
Section: Fig 1 Cancer Cachexia Is a Multifactorial Syndromementioning
confidence: 99%
“…In a recent report by Hentilä et al, the blockade of activin receptor type 2 (ACVR2) ligands (e.g., myostatin, activins, and TGFb) by the recombinant soluble activin receptor 2B (sACVR2B-Fc) has been proven to modulate the redox balance in healthy and tumor-bearing animals (57). In the latter, sACVR2B-Fc protects against muscle wasting, increasing survival and correcting GSH reduction and GSSG/GSH ratio increase (57,87). Along with these effects, the soluble activin receptor increases the expression of heat shock protein 25 (HSP25) (57), which is involved in glutathione metabolism and resistance to ROS (43).…”
Section: Fig 5 Exercise Modu-mentioning
confidence: 99%
“…Indeed, it was recently reported that the same treatment used in our work attenuated hepatic protein synthesis and splenomegaly in a rodent cachexia model that were independent of changes in muscle phenotype. 79 We are nevertheless mindful that despite promising results in rodent models, translation of therapies based on myostatin/activin antagonists have been, to date, unsuccessful in delivering intended outcomes and others have been curtained due to safety concerns 80,81 and point to the need to develop a greater understanding of the biological processes controlled by this signalling axis. A possible means of alleviating some of the safety issues associated with myostatin/activin antagonists could be through decreasing their dose but at the same time harnessing the benefits of other agents that promote healthy ageing.…”
Section: Compression Of Morbidity By Soluble Activin Receptor Type IImentioning
confidence: 99%